2004
DOI: 10.1158/1078-0432.ccr-050004
|View full text |Cite
|
Sign up to set email alerts
|

Review of Radiofrequency Ablation for Renal Cell Carcinoma

Abstract: This review will discuss how minimally invasive, imageguided radiofrequency (RF) tumor ablation [i.e., coagulating tumor using short-duration heating (<15 minutes) by directly applying temperatures >50°C via needle electrodes] is being incorporated as a clinical tool for the treatment of renal cell carcinoma. RF ablation has been used to treat focal liver tumors. Potential benefits of this thermal therapy include reduced morbidity and mortality compared with standard surgical resection and the ability to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 59 publications
1
25
0
1
Order By: Relevance
“…Although various complications have been reported, the majority of those were minor and the complication rates were low (30,31). In the present study, complications were observed in five sessions following RFA (10%).…”
Section: Discussionmentioning
confidence: 41%
“…Although various complications have been reported, the majority of those were minor and the complication rates were low (30,31). In the present study, complications were observed in five sessions following RFA (10%).…”
Section: Discussionmentioning
confidence: 41%
“…Imaging immediately after the procedure can be difficult to interpret because periablation inflammation may mimic the appearance of a residual viable tumor (Hines-Peralta & Goldberg, 2004). A definition of complete coagulation necrosis and thus a completely ablated tumor after RF ablation is the absence of enhancement on CT or MR images.…”
Section: Outcomes 451 Therapeutic Efficacymentioning
confidence: 99%
“…The question of whether RITA-induced tissue lesions are truly necrotic in nature also remains to be clarified. Indeed, as Dr S Nahun Goldberg said in the opening comments of a recent article 2 'there is no question that one can achieve (y) mummification of the cells that are in fact dead, but because they don't show signs of coagulative necrosis or the absence of nuclei, many pathologists have originally called these cells live'. The author is referring to liver neoplasms, like much of the available data on RF treatments.…”
Section: Histopathological Findings After Rfmentioning
confidence: 99%
“…[1][2][3] Temperatures above 601C have a rapid cytotoxic effect due to protein coagulation. 1 The amount of heat energy produced and the subsequent thermal effect are determined by the amount of tissue contact (the length of the needle) and the wattage.…”
Section: Introductionmentioning
confidence: 99%